(untitled) (Revista Contexto & Educação, 2023)
Early Childhood, a period that comprises the first six years of life, is a stage in which intense changes in brain structure and functioning are observed. Research indicates that during the first years of life the brain architecture is formed and it allows learnings from this period to fund development in subsequent stages. This study is characterized as a qualitative research, using a bibliographic review in authors from the areas of Neuroscience and Education in order to provide transdisciplinary knowledge that can promote clarifications about development and learning in Early Childhood. This research points out that knowledge about terms such as neuroplasticity, stimuli, emotion and memory favors the dialogue between Neurosciences and Education, besides collaborating to clarify the theme to teachers who teach to children in Early Childhood Education, fostering the development of pedagogical practices that consider brain functioning in Early Childhood.